High-strength polishing pad with embedded abrasive grains

JP7604696B1Active Publication Date: 2024-12-23NORITAKE MACHINE TECHNO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024041722
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2024-12-23
Estimated Expiration
2044-03-15

Smart Images

  • Figure 0007604696000001_ABST
    Figure 0007604696000001_ABST
Patent Text Reader

Abstract

To provide a polishing pad having strength not to be broken even when polishing is performed by increasing the polishing pressure of a workpiece in order to improve polishing efficiency. [Solution] Hollow resin spheres 38 are arranged three-dimensionally in the polishing pad 18, and the hollow spheres 38 are bonded with a matrix resin 40, and the communicating spaces 42 between the hollow spheres 38 are filled with polishing grains 36. As a result, the hollow spheres 38 bonded with the matrix resin 40 form a wall structure, and the polishing pad 18 has a strength that does not break even when the polishing pressure of the workpiece 16 is increased and high-load polishing is performed. In addition, in this polishing pad 18, the hollow spheres 38 in the polishing pad 18 convert the vertical pressure received from the workpiece 16 into lateral pressure by deformation, and push the polishing grains 36 to the surface layer of the polishing pad 18, thereby increasing the polishing grains 36 on the polishing surface, and the active abrasive grains 36a in contact with the workpiece 16 are increased, and the polishing rate PR is increased.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an abrasive grain-containing polishing pad used for polishing one side of a workpiece such as a glass substrate or a semiconductor substrate, and relates to a high-strength polishing pad that enables high-load polishing processing. [Background technology]

[0002] Abrasive-containing polishing pads are known that have a porous base resin having interconnected pores and a large number of abrasive grains contained in the longitudinal interconnected pores formed in the base resin. Such abrasive-containing polishing pads are also called LHA (Loosely Held Abrasive) pads, and do not use a slurry containing abrasive grains as a polishing liquid, so that the consumption of abrasive grains is small and the environmental load is reduced. For example, the abrasive-containing polishing pads described in Patent Document 1 and Patent Document 2 are such abrasive-containing polishing pads.

[0003] In such an abrasive-containing polishing pad described in Patent Document 1, abrasive grains are self-supplied between the polishing pad and the workpiece, so when used in CMP (chemical mechanical polishing) methods, there is no need to use a slurry containing expensive abrasive grains, thereby reducing the uneconomical and environmentally friendly disposal of used slurry.

[0004] The abrasive grain-containing polishing pad described in Patent Document 2 is provided with a porous base resin having interconnected pores, a large number of abrasive grains contained in longitudinal interconnected pores formed in the base resin, and large-diameter pores formed between the interconnected pores by the base resin and having a larger cross-sectional area than the interconnected pores. When pressure is applied during polishing, the abrasive grains contained in the interconnected pores move into the large-diameter pores connected to the interconnected pores due to a micro-pumping effect (an effect in which the polishing pad is pressed by pressure and the abrasive grains in the interconnected pores are pushed toward the large-diameter pores), and a large number of abrasive grains are retained in the large-diameter pores on the surface, increasing the number of active abrasive grains that come into contact with the underside of the workpiece, thereby improving the polishing efficiency. This effect is prominent in the case of abrasive grains that are difficult to move due to their irregular (non-spherical) shape, such as ceria particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-025415 A [Patent Document 2] JP 2011-049256 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the abrasive grain-containing polishing pads described in Patent Documents 1 and 2, the base resin is columnar (fibrous) in order to form longitudinally communicating pores that contain the abrasive particles, so when the polishing pressure of the workpiece is increased to increase the polishing efficiency, the strength of the base resin may be insufficient, causing the polishing pad to break and making polishing difficult.

[0007] The present invention has been made against the background of the above circumstances, and its object is to provide an abrasive grain-containing polishing pad that has the strength to withstand high load polishing by increasing the polishing pressure on the workpiece in order to improve polishing efficiency.

[0008] The inventor of the present invention has conducted various studies in the light of the above circumstances, and as a result, has found that by arranging hollow resin spheres (microballoons) three-dimensionally in an abrasive grain-containing polishing pad, bonding the hollow spheres with a matrix resin, and filling the spaces between the hollow spheres with abrasive grains, the hollow spheres bonded with the matrix resin form a wall structure, and even when the polishing pressure of the workpiece is increased and high-load polishing is performed, a highly strong abrasive grain-containing polishing pad can be obtained. In addition, in an abrasive grain-containing polishing pad of this structure, the hollow spheres in the polishing pad convert the vertical pressure received from the workpiece into lateral pressure by deformation, and push the abrasive grains to the surface layer of the polishing pad, thereby increasing the number of abrasive grains on the polishing surface, and the inside of the hollow spheres opening to the polishing surface becomes a reservoir where the abrasive grains are retained and supply the abrasive grains between the polishing pad and the workpiece, and the number of active abrasive grains that come into contact with the workpiece increases, thereby improving the polishing efficiency. The present invention has been made based on such findings. [Means for solving the problem]

[0009] That is, the gist of the first invention is a high-strength polishing pad containing abrasive grains, which is used for polishing one surface of a workpiece by a CMP method, and which comprises hollow spheres made of resin, a base resin that bonds the hollow spheres, and polishing grains filled in the communicating spaces between the hollow spheres. The base resin is made of a hydrophilic resin, and the hollow sphere is made of a non-hydrophilic resin, and the hydrophilic resin is a polyethylene glycol-based acrylic resin. The point is that.

[0012] No. 2 The gist of the invention is as follows: 1 In the present invention, the monomer of the polyethylene glycol-based acrylic resin before curing of the base resin is a combined resin of polyethylene glycol diacrylate and dipentaerythritol hexaacrylate.

[0013] No. 3 The gist of the invention is as follows: 1 In the present invention, the non-hydrophilic resin is an acrylic resin or a vinylidene chloride resin.

[0014] No. 4The gist of the invention is that in the first invention, the polishing abrasive grains are at least one of ceria, manganese oxide, silica, alumina, titania, zirconia, and iron oxide. Effect of the Invention

[0015] According to the first invention, hollow spheres (microballoons) made of resin are arranged three-dimensionally in the abrasive grain-containing high-strength polishing pad, and the hollow spheres are bonded with a matrix resin, and the spaces between the hollow spheres are filled with abrasive grains. As a result, the hollow spheres bonded with the matrix resin form a wall structure, and a high-strength abrasive grain-containing high-strength polishing pad is obtained that is not broken even when the polishing pressure of the workpiece is increased and high-load polishing is performed. In addition, in the high-strength polishing pad containing abrasive grains of this structure, the hollow spheres in the polishing pad convert the vertical pressure received from the workpiece into lateral pressure by deformation, and push the abrasive grains to the surface layer of the polishing pad, thereby increasing the amount of abrasive grains on the polishing surface, and the inside of the hollow spheres opening to the polishing surface becomes a reservoir where the abrasive grains are retained and supply the abrasive grains between the polishing pad and the workpiece, so that the amount of active abrasive grains that come into contact with the workpiece increases, and the polishing efficiency is improved. In addition, since the base resin is made of a hydrophilic resin and the hollow spheres are made of a non-hydrophilic resin, during polishing processing using an aqueous polishing liquid, the base resin softens but the hollow spheres do not soften, thereby maintaining the strength of the high-strength polishing pad. Furthermore, since the hydrophilic resin is a polyethylene glycol-based acrylic resin, the base resin has appropriate elasticity when polishing with an aqueous polishing liquid, and therefore, by repeatedly pressing the workpiece, a micro-pumping effect is preferably obtained, which pushes the polishing grains to the surface.

[0018] No. 2 According to the abrasive grain-containing high-strength polishing pad of the present invention, the monomer of the polyethylene glycol-based acrylic resin before the base resin hardens is a combination resin of polyethylene glycol diacrylate and dipentaerythritol hexaacrylate. This allows the base resin to have an appropriate hardness, so that the polishing rate and polished surface roughness can be favorably obtained.

[0019] No. 3 According to the abrasive grain-containing high-strength polishing pad of the present invention, the non-hydrophilic resin constituting the hollow sphere is an acrylic resin or a vinylidene chloride resin, so that the hollow sphere does not soften during polishing with an aqueous polishing liquid, and a high-strength abrasive grain-containing high-strength polishing pad having high strength and not broken even when polishing with a high load is obtained.

[0020] No. 4 According to the abrasive grain-containing high-strength polishing pad of the invention, the abrasive grains are at least one of ceria, manganese oxide, silica, alumina, titania, zirconia, and iron oxide. In particular, even with abrasive grains having an irregular (non-spherical) shape such as ceria, the abrasive grains in the communicating space are pushed toward the large-diameter pores by the micro-pumping action caused by the repeated elastic deformation of the hollow sphere. [Brief description of the drawings]

[0021] [Figure 1] 1 is a perspective view conceptually showing the configuration of a polishing device to which an abrasive grain-containing polishing pad according to one embodiment of the present invention is applied; [Diagram 2] 2 is a plan view for explaining a rotation hole of an attachment disk of the polishing device of FIG. 1.

[0023] FIG. [Diagram 3] 2 is a SEM photograph of a cross section for explaining the configuration of a polishing pad having hollow spheres used in the polishing apparatus of FIG. 1. FIG. [Figure 4] 2 is a cross-sectional view for explaining a schematic configuration of the polishing pad having the hollow sphere of FIG. 1. [Diagram 5] 2 is a schematic diagram illustrating the micro-pumping action of the polishing pad having the hollow sphere of FIG. 1. [Figure 6] FIG. 2 is a diagram showing the composition ratio of the polishing pad having hollow spheres in FIG. 1 in comparison with the polishing pad having large pores in Patent Document 2. [Figure 7] FIG. 2 is a diagram showing the basic chemical structure of a hydrophilic resin constituting a base resin in the abrasive grain-containing polishing pad of FIG. [Figure 8] FIG. 2 is a diagram showing the chemical structure of dipentaerythritol hexaacrylate (monomer), which is a material constituting the hydrophilic resin constituting the base resin in the abrasive grain-containing polishing pad of FIG. [Figure 9] FIG. 2 is a diagram showing the chemical structure of PEG400#diacrylate (n=9), which is a material constituting the hydrophilic resin constituting the base resin in the abrasive grain-containing polishing pad of FIG. [Figure 10] FIG. 2 is a diagram showing the chemical structure of PEG600#diacrylate (n=14), which is a material constituting the hydrophilic resin constituting the base resin in the abrasive grain-containing polishing pad of FIG. [Figure 11] 1 is a table showing the results of an evaluation conducted by the present inventors of the combination ratio of dipentaerythritol hexaacrylate and PEG400# diacrylate (n=9) or PEG600# diacrylate (n=14) and the polishing ability of the polishing pad. [Figure 12] 4A to 4C are process diagrams illustrating the manufacturing process of the polishing pad. [Figure 13] FIG. 1 is a graph showing changes in polishing rate during polishing tests of polishing pads with different polishing loads conducted by the present inventors, in comparison with the polishing pad of Patent Document 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] An embodiment of the present invention will be described in detail below with reference to the drawings. Note that in the following embodiment, the drawings are appropriately simplified or modified, and the dimensional ratios and shapes of the various parts are not necessarily drawn accurately. EXAMPLES

[0023] Fig. 1 conceptually shows the main part of a surface polishing apparatus 10 to which an abrasive grain-containing high-strength polishing pad (hereinafter referred to as a polishing pad) 18 according to one embodiment of the present invention is applied, with a guide roller fixing base 28 removed. In Fig. 1, a polishing platen 12 is provided in the surface polishing apparatus 10 and supported so as to be rotatable about a vertical rotation axis C1, and the polishing platen 12 is rotated at a constant speed in one rotation direction indicated by an arrow in Fig. 1 by a platen driving motor 14. A polishing pad 18 having a diameter of, for example, about 300 mmφ is attached to the upper surface of the polishing platen 12, i.e., the surface against which one surface of a workpiece (glass plate or semiconductor substrate) 16 is pressed.

[0024] The workpiece 16 is held on the lower surface of the application disc 20, i.e., the surface facing the polishing pad 18, and the application disc 20 presses the workpiece 16 against the polishing pad 18 with a predetermined load. A drip nozzle 22 is provided near the application disc 20 of the surface polishing device 10, and a polishing liquid (lubricant) 26 not containing abrasive grains is delivered from a polishing liquid supply device 24 and supplied onto the polishing surface plate 12. When the workpiece 16 is a glass plate, water is used as the polishing liquid 26.

[0025] In addition, the surface polishing apparatus 10 is provided, as necessary, with an adjustment tool holding member (not shown) that is arranged to be rotatable about a rotation axis C1 parallel to the rotation axis C1 of the polishing table 12 and to be movable in the direction of the rotation axis C1 and in the radial direction of the polishing table 12, and an abrasive body adjustment tool (dresser or conditioner) such as a diamond wheel (not shown) that is attached to the lower surface of the adjustment tool holding member, i.e., the surface facing the polishing pad 18. The adjustment tool holding member and the abrasive body adjustment tool attached thereto are pressed against the polishing pad 18 while being rotated and driven by an adjustment tool driving motor (not shown), and are reciprocated in the radial direction of the polishing table 12, thereby adjusting the polishing surface of the polishing pad 18 and constantly maintaining the surface state of the polishing pad 18 in a state suitable for polishing.

[0026] 2, at a position eccentric from the rotation axis C1 on the polishing table 12, the outer peripheral surface of a short cylindrical attachment disk 20, which holds the workpiece 16 to be polished on its underside by suction, adhesion, or a holding frame, is received by a pair of rotatable guide rollers 30 and a drive guide roller 32 provided on a guide roller fixing base 28, which is fixed in a position fixed to a frame (not shown), so that the attachment disk 20 can rotate about the rotation axis C2. The attachment disk 20 is rotated about the rotation axis C2 by receiving a rotational force based on the difference in peripheral speed between the polishing table 12 or the polishing pad 18, and the attachment disk 20 is pressed against the polishing pad 18 on the polishing table 12 by the load of, for example, a weight 34, thereby polishing the workpiece 16.

[0027] The following polishing method is applied to polishing by the surface polishing device 10. That is, the polishing table 12 and the polishing pad 18 attached thereto, the attachment disk 20 and the workpiece (silicon wafer) 16 held on the lower surface thereof are rotated around the rotation axis C1 and the rotation axis C2 by the table drive motor 14 and the drive guide roller 32, respectively, while the polishing liquid 26 not containing abrasive grains is supplied onto the surface of the polishing pad 18 from the drip nozzle 22 and a spray nozzle (not shown). As a result, the surface to be polished of the workpiece 16, i.e., the surface facing the polishing pad 18, is polished flat by the mechanical polishing action of the polishing grains 36 contained in the polishing pad 18 and self-supplied from the polishing pad 18. When the workpiece 16 is a glass plate, ceria is used as the polishing grains 36.

[0028] As shown in the SEM photograph of FIG. 3 and the schematic diagram of FIG. 4, the polishing pad 18 attached on the polishing platen 12 includes a matrix resin 40 that bonds hollow spheres 38 arranged three-dimensionally in the polishing pad 18, and polishing grains 36 filled in the communication spaces 42 formed by the matrix resin 40 between the hollow spheres 38. The hollow spheres (microballoons) 38 are hollow and made of a non-hydrophilic resin such as an acrylic resin or a vinylidene chloride resin. The particle diameter of the hollow spheres 38 is, for example, 20 μmφ to 60 μmφ, and the particle diameter of the polishing grains 36 is, for example, 6 nmφ to 1720 nmφ. The polishing grains 36 are selected from at least one of ceria, manganese oxide, silica, alumina, titania, and zirconia. In FIG. 3, 38s indicates the shell of the hollow spheres 38.

[0029] In the polishing pad 18 having the hollow spheres 38 thus constructed, the hollow spheres 38 are bonded together in close proximity to each other to form a relatively rigid wall structure, and thus the strength is increased. In this way, the hollow spheres 38 bonded together by the matrix resin 40 form a wall structure, and therefore the polishing pad 18 has high strength and is not broken even when the polishing pressure of the workpiece 16 is increased to perform high-load polishing. As shown in FIG. 5, the hollow spheres 38 in the polishing pad 18 convert the vertical pressure received from the workpiece 16 into lateral pressure by their elastic deformation, and push the polishing grains 36 to the surface layer of the polishing pad 18, thereby increasing the polishing grains 36 on the polishing surface, and the inside of the hollow spheres 38 that open to the polishing surface becomes a reservoir where the polishing grains 36 are retained and supplied between the polishing pad 18 and the workpiece 16, and therefore the number of working abrasive grains that come into contact with the lower surface of the workpiece 16 increases, contributing to high polishing efficiency.

[0030] The base resin 40 is made of a hydrophilic resin, such as a polyethylene glycol-based acrylic resin, and the hollow spheres 38 are made of a non-hydrophilic resin, such as an acrylic resin or a vinylidene chloride resin. During polishing using an aqueous polishing liquid 26, the base resin 40 softens, but the hollow spheres 38 do not, so the strength of the high-strength polishing pad is maintained. As a result, the base resin 40 is appropriately softened, and as shown in FIG. 5, when the polishing pad 18 is repeatedly pressed against the workpiece 16, the hollow spheres 38 elastically deform into a horizontally elongated shape, and the polishing grains 36 contained in the communicating spaces 42 of the base resin 40 are pushed out to the surface layer of the polishing pad 18, thereby providing a micropumping effect.

[0031] The polishing pad 18 of this embodiment has, for example, the volume ratio shown in Fig. 6. Fig. 6 shows a comparison with a polishing pad of a conventional structure described in Patent Document 2 (comprising a porous base resin having communicating pores, a large number of abrasive grains contained in longitudinal communicating pores formed in the base resin, and large-diameter pores formed between the communicating pores by the base resin and having a cross-sectional area larger than that of the communicating pores). The polishing pad 18 of this embodiment does not have a significant difference in the volume of abrasive grains compared to the polishing pad with large pores of Patent Document 2, but the volume of the base resin (PEG400# diacrylate (n=9) used) 40 is more than twice the volume of the base resin (PES resin) of the polishing pad of Patent Document 2, the volume of the hollow sphere 38 is slightly larger, about 1.2 times the volume of the large pores of the polishing pad of Patent Document 2, the volume of the communicating space 42 is less than 1 / 3 the volume of the communicating pores of the polishing pad of Patent Document 2, and the hardness of the polishing pad 18 measured with a durometer hardness tester is about 1.5 times higher than the hardness of the polishing pad of Patent Document 2.

[0032] The base resin 40 is composed of a polyethylene glycol-based acrylic resin having, for example, the chemical structure shown in FIG. 7. The monomer of this polyethylene glycol-based acrylic resin is a combination resin of dipentaerythritol hexaacrylate (monomer) shown in FIG. 8 and PEG400# diacrylate (n=9) shown in FIG. 9 or PEG600# diacrylate (n=14) shown in FIG. 10. According to tests by the inventors, these combinations are preferably such that the ratio of dipentaerythritol hexaacrylate is 10 vol% to 20 vol%, as shown in FIG. 11. If the ratio of dipentaerythritol hexaacrylate is 0 vol%, the base resin 40 swells, and if the ratio of dipentaerythritol hexaacrylate is 100 vol%, the base resin 40 becomes hard, and neither is suitable for polishing.

[0033] FIG. 12 is a process diagram for explaining the manufacturing process of the polishing pad 18. In FIG. 12, in the resin preparation step P1, dipentaerythritol hexaacrylate and PEG400# diacrylate (n=9), which are materials of the base resin 40, are prepared and mixed so that the ratio of dipentaerythritol hexaacrylate is 10 vol% to 20 vol%. Next, in the polymerization initiator mixing step P2, the polymerization initiator AIBN is mixed into the prepared resin, and in the subsequent resin stirring step P3, the polymerization initiator AIBN and the prepared resin are stirred. Next, in the abrasive grain mixing step P4, the polishing abrasive grains (ceria) 36 are introduced and stirred, and then, in the hollow sphere mixing step P5, the hollow spheres 38 are introduced and stirred to form a slurry. Next, in the molding step P6, the material is molded into a plate shape of a predetermined thickness using a casting molding method or a doctor blade method. Then, in the curing step P7, the polymerization of the resin is accelerated by heating, and the slurry molded to a predetermined thickness is cured.

[0034] (Experimental Example) Below, we will explain the polishing test that the inventor conducted under polishing test conditions using polishing pad 18 to measure the change over time in the polishing rate PR (μm / min) of polishing pad 18, with the pressing load of workpiece 16 against polishing pad 18 as a parameter.

[0035] (Polishing test conditions) Equipment: 380mmφ single-sided polishing machine Workpiece: Synthetic quartz (100mmφ×1mmt) [1 piece] Plate rotation speed: 60 rpm Workpiece rotation speed: 60 rpm Test time: 300 min Polishing liquid: Water (city water) (10ml / min) Dresser: Diamond pellet (#400) for 2 minutes before polishing test Polishing pad: Abrasive grain-containing high-strength polishing pad (abrasive grain: average primary particle diameter 27 nmφ [measured by laser type particle size distribution measuring device, particle diameter D10 = 6 nmφ, D50 = 0.78 nmφ, D90 = 1.72 nmφ] ceria 17.9 vol%, hollow sphere: average particle outer diameter 40 μmφ acrylic resin 34.2 vol%, base resin: polyethylene glycol acrylic resin 36.4 vol%, hardness: 60.5 (durometer hardness Type-D))

[0036] FIG. 12 shows the polishing rate PR (μm / min) measured over time when polishing was performed under the above polishing conditions using the conventional abrasive-containing polishing pad described in Patent Document 2 and the high-strength abrasive-containing polishing pad (polishing pad 18) of this embodiment at two different polishing loads (20 kPa and 40 kPa). In FIG. 12, the polishing rate PR when the conventional abrasive-containing polishing pad described in Patent Document 2 was used at polishing loads of 20 kPa and 40 kPa is shown by △ and ▲ marks. In addition, the polishing rate PR when the high-strength abrasive-containing polishing pad of this embodiment was used at polishing loads of 20 kPa and 40 kPa is shown by ○ and ● marks. According to FIG. 12, when the polishing load was 20 kPa, there was not much difference between the polishing rate PR of the conventional abrasive-containing polishing pad and the polishing rate PR of the high-strength abrasive-containing polishing pad of this embodiment. However, when the polishing load was 40 kPa, the polishing rate PR of the conventional structured abrasive-containing polishing pad was higher than that of the polishing load of 20 kPa, but the polishing pad was damaged after 30 min of polishing. In contrast, the abrasive-containing high-strength polishing pad of this embodiment obtained a polishing rate PR of about 1.8 times that of the polishing load of 20 kPa until 300 min of polishing. In other words, the abrasive-containing high-strength polishing pad of this embodiment enables high-load and high-efficiency polishing.

[0037] As described above, according to the polishing pad 18 of this embodiment, hollow resin spheres (microballoons) 38 are arranged three-dimensionally within the polishing pad 18, and the hollow spheres 38 are bonded with a matrix resin 40, and the abrasive grains 36 are filled into the communicating spaces 42 between the hollow spheres 38. As a result, the hollow spheres 38 bonded with the matrix resin 40 form a wall structure, and an abrasive grain-containing high-strength polishing pad 18 is obtained that has high strength and will not break even when the polishing pressure of the workpiece 16 is increased to perform high-load polishing. Furthermore, in the abrasive-containing high-strength polishing pad 18 having such a structure, the hollow spheres 38 inside the polishing pad 18 convert the vertical pressure received from the workpiece 16 into lateral pressure through their deformation and push the polishing grains 36 out to the surface of the polishing pad 18, thereby increasing the amount of polishing grains 36 on the polishing surface, and the inside of the hollow spheres 38 opening to the polishing surface serves as a reservoir where the polishing grains 36 remain and supply the polishing grains 36 between the polishing pad 18 and the workpiece 16, so that the amount of active abrasive grains 36a that come into contact with the workpiece 16 increases and the polishing rate PR is improved.

[0038] In the polishing pad 18 of this embodiment, the base resin 40 is made of a hydrophilic resin, and the hollow spheres 38 are made of a non-hydrophilic resin. Therefore, during polishing using the aqueous polishing liquid 26, the base resin 40 softens, but the hollow spheres 38 do not, so the strength of the polishing pad 18 is maintained.

[0039] According to the polishing pad 18 of this embodiment, the base resin 40 is a polyethylene glycol-based acrylic resin, and therefore, when polishing with the aqueous polishing liquid 26, the base resin 40 has an appropriate elasticity, and therefore, by repeatedly pressing the workpiece 16, a micro-pumping effect is preferably obtained that pushes the polishing grains 36 to the surface.

[0040] In the polishing pad 18 of this embodiment, the monomer of the polyethylene glycol-based acrylic resin before hardening of the base resin 40 is a combination resin of polyethylene glycol diacrylate and dipentaerythritol hexaacrylate. This provides the base resin 40 with an appropriate hardness, so that the polishing rate PR and the polished surface roughness can be favorably obtained.

[0041] In the polishing pad 18 of this embodiment, the non-hydrophilic resin constituting the hollow spheres 38 is an acrylic resin or a vinylidene chloride resin. This prevents the hollow spheres 38 from softening during polishing with the aqueous polishing liquid 26, and provides the polishing pad 18 with high strength that is not broken even when polishing with a high load is performed.

[0042] In the polishing pad 18 of this embodiment, the polishing grains 36 are at least one of ceria, manganese oxide, silica, alumina, titania, zirconia, and iron oxide. In particular, even if the polishing grains 36 are irregular (non-spherical) in shape, such as ceria particles, the polishing grains 36 in the communication spaces 42 are pushed toward the large-diameter pores by the micro-pumping action caused by repeated elastic deformation of the hollow spheres 38.

[0043] Although one embodiment of the present invention has been described above, the present invention can be applied in other aspects.

[0044] For example, in the surface polishing apparatus 10 of the above embodiment, the polishing liquid 26 is aqueous, but it may be a polishing liquid made of an organic amine and water, or an organic amine, an alkaline agent, and water.

[0045] Furthermore, although a polyethylene glycol-based acrylic resin was used for the base resin 40, other hydrophilic resins may also be used, such as PES resin having a hydrophilic group, rigid foamed polyurethane resin, polyamide, polyamideimide, polyimide, polyacrylonitrile, polyvinylidene fluoride, cellulose acetate, polyvinyl alcohol, polyvinyl acetate, polyethylene glycol (molecular weight of 1000 or more), polyester, polyolefin-based resin, non-foamed polyurethane, and PVA.

[0046] Further, although acrylic resin or vinylidene chloride resin is used for the hollow sphere 38, other non-hydrophilic resins may also be used.

[0047] Although not specifically illustrated, the present invention can be used with various modifications within the scope of the invention. [Explanation of symbols]

[0048] 16: workpiece, 18: polishing pad (high-strength polishing pad containing abrasive grains), 36: polishing grains, 38: hollow sphere, 40: base resin, 42: communicating space

Claims

1. A high-strength polishing pad containing abrasive grains for use in polishing one surface of a workpiece by a CMP method, A hollow resin sphere; A matrix resin that bonds the hollow spheres; abrasive grains filled in the communicating spaces between the hollow spheres; the matrix resin is made of a hydrophilic resin, and the hollow sphere is made of a non-hydrophilic resin; The hydrophilic resin is a polyethylene glycol-based acrylic resin. A high-strength polishing pad containing abrasive grains.

2. The monomer of the polyethylene glycol-based acrylic resin before curing of the base resin is a combination resin of polyethylene glycol diacrylate and dipentaerythritol hexaacrylate.

2. The high-strength polishing pad according to claim 1, wherein the abrasive grains are contained therein.

3. The non-hydrophilic resin is an acrylic resin or a vinylidene chloride resin.

2. The high-strength polishing pad according to claim 1, wherein the abrasive grains are contained therein.

4. The abrasive grains are at least one of ceria, manganese oxide, silica, alumina, titania, zirconia, and iron oxide.

2. The high-strength polishing pad according to claim 1, wherein the abrasive grains are contained therein.

Citation Information

Patent Citations

  • JP1992097650U

  • Resin bond grinding wheel

    JP1993277956A

  • Resinoid grinding wheel

    JP1999156725A

  • Polishing tool and manufacturing method therefor

    JP2003011066A

  • Polishing body and its manufacturing method

    JP2004025415A